Arrested Eruption in Human Primary Molars: A Case Series Study, Based on Radiological and Histochemical Investigations on Primary Molars from 24 Children - Inger Kjær (Journal of Dental Health and Oral Research, 2026)
Aim and objectives: The main purpose of this study is to describe histochemical observations in the human periodontal area of primary molars, with arrested eruption, diagnosed clinically or radiographically. Methods: 24 primary molars extracted from children 4-10 years old, diagnosed clinically and radiologically with arrestment in eruption are presented. The teeth were forwarded to the Department of Odontology, University of Copenhagen from municipal paediatric dental clinics. In only seven cases, radiographs (orthopantomograms) documenting arrest were enclosed for analysis. The material was divided into two groups. Group 1: The 7 cases containing radiographs. Group 2: The 17 cases without radiographs. All 24 primary molars were fixed in formalin and analysed histochemically. After decalcification, paraffin-embedding and sectioning were performed. Sections were coloured with toluidine blue or according to the Van Gieson method. The sectioning of each tooth allowed observations in the microscope in the cutting plane only. Results: The study demonstrates that the periodontal membrane in arrested primary molars has the ability to react differently during arrested eruption. The resorption defect in the root dentine was in few cases covered by bone apposition. In one case the periodontal membrane had disappeared between the jawbone and the root dentine. The radiographs did not reveal these differences. Conclusion: The monocellular hematopoietic precursor cells in the periodontal membrane of the primary molars have the well-known ability to develop to osteoclasts, ex. during resorption, but also the ability to develop to osteoblasts. How and why these different cell developments influence arrestment, is not known.